On the Possibility of (Un)Naming God: Thinking Theologically Along the Lines of Literature - Hall, W. David (Literature and theology, 2015)
Through a critical analysis of the ideas of Jean-Luc Marion, Paul Ricoeur, and Maurice Blanchot, this article argues for the need to think theologically 'along the lines' of literature. I do not claim that theology is literature, or literary criticism, but that new possibilities open up in light of an encounter with what theology shares with literature: the capacity to articulate a revelatory event. I conclude with the suggestion that theological discourse is a kind of self-conscious idolatry that strives to de-nominate God, a conscious naming of the divine that simultaneously recognises the inadequacy of those names.